Effect of rooting hormones on the rooting capability of Ficus benjamina L. cuttings - Topacoglu, Osman; Sevik, Hakan; Guney, Kerim; Unal, Canan; Akkuzu, Erol; Sivacioglu, Ahmet (Croatian Forestry Society, 2016)
Tehnike vegetativne proizvodnje od kojih se metoda reznica uvelike koristi u razmnožavanju ukrasnog bilja, imaju ključnu ulogu za očuvanje genetskih izvora biljaka. Mjesto uzimanja reznice na biljci, medij ukorjenjivanja i fitohormon ukorjenjivanja neki su od ključnih čimbenika koji utječu na uspjeh razvoja zakorjenjivanja reznica od stabljike. Primarni cilj ovog istraživanja bio je utvrditi najbolje koncentracije fitohormona i idealni medij zakorjenjivanja za reznice od stabljike vrste Ficus benjamina L. Konvencionalno, najčešća metoda vegetativnog razmnožavanja je zakorjenjivanja pupova u različitim supstratima kao što su perlit, treset, pijesak do izloženosti visoko koncentriranim hormonima zakorjenjivanja (IBA, IAA, NAA, itd.). Ali ta konvencionalna tehnika zahtijeva široka područja u fazi zakorjenjivanja masovne produkcije, sprječava nadzor tijeka zakorjenjivanja i traži visoku količinu materijala koji se koriste kao hormoni i mediji zakorjenjivanja. U ovom istraživanju, ispitana je nova metoda koja bi mogla biti poželjnijom u masovnoj proizvodnji biljaka. Izvršeno je 39 različitih tretiranja i prikazani su njihovi rezultati. Pijesak i perlit korišteni su kao kruti medij zakorjenjivanja. Pupovi su se trajno čuvali u hormonima niske koncentracije nakon rezanja (tekući medij). Na taj način je ispitana njihova sposobnost zakorjenjivanja. Ispitivanja zakorjenjivanja provedena su prije nego su pupovi odnijeti u kruti medij zakorjenjivanja. Kao zaključak, dobiveni su najviši omjeri zakorjenjivanja za 10 ppm NAA (94.43%) te 100 ppm IBA (93.9%) u tekućim medijima. Najveća duljina korijena i prosječna duljina korijena bile su prilično male u tekućim medijima.

Vegetative production techniques, of which cutting method widely used in propagation of ornamental plants, have a crucial role for conserving the plant genetic sources. On rooting development of stem cuttings, cutting position, rooting medium and rooting hormone are some of the critical factors that affect the success. The primary objective of this study is to determine the best hormone doses and ideal rooting medium on Ficus benjamina L. stem cuttings. Conventionally, the most frequently vegetative propagation method is the rooting of the stem cuttings in various media such as, pearlite, peat, sand, through exposure to high-concentration rooting hormones (IBA, IAA, NAA, etc.). But, this conventional technique requires wide areas in the rooting stage of mass production, prevents monitoring the course of rooting, and necessitates large amount of materials used as hormones and rooting media. In this study, a new method that may be preferable in mass production of plants was tested. 39 different treatments were carried out, and their results were evaluated. Sand, and perlite were used as solid rooting media. Stem cuttings were kept in low-concentration hormones permanently after cutting (liquid medium). In this way, their rooting capability were examined. Rooting trials were conducted before stem cuttings were taken to solid rooting media. As conclusions, the highest rooting ratio were obtained for 10 ppm of NAA (94.43%) and 100 ppm of IBA (93.9%) in liquid media. Moreover, the highest root length and the average root length were quite low in liquid media.
Keywords: auksini; fitohormones; rooting; fitohormoni; vegetative propagation; auxins; autovegetativno razmnožavanje; zakorjenjivanje